Uso corporativo do território e turismo no Rio Grande do Norte - Costa, Jordana Medeiros (2011)
Tourism has in recent years a significant growth in the economy, bringing repercussions on use of the territory. Hence the importance of discussing how the activity has been planned by public authorities and business, important actor in this process. Our objective is to analyze the corporative use of the territory Norte-Rio-Grandense by tourism, based on the renewal of geographical thought in Milton Santos and other authors coherent theory. Although planning is seen as a practice that incorporates various scientifics contributions is undeniable eminently geographical base, as it comes to relationshipsand process in the territory. The project Parque das Dunas/Via Costeira driving the development of tourism in Natal as to its construction, the city had a quality hotel infrastructure capable of receiving a greater number of tourists. One of the guiding instruments of state planning in accordance with the Federal Government is the Planejamento Pluri-Anual - PPA, which has the discourse territory, but establishes sectoral actions, which included tourism with the allocation of resources. In addition to receiving funds Prodetur I and II, since the early 1990s, these resources from the BIRD and other lines of funding available through federal financial institutions. Thus the sectoral action planning is disintegrated, while the territorial planning makes us think the whole moving and complexity Our data policies and public and private investments, we proved that the action of companies in line with the state, favors the hegemonic agents, or the corporative use of the territory Norte-Rio-Grandense